Specific but not global cognitive functions are associated with gait initiation in older adults - Sirinun Boripuntakul (2018)
© 2017 Human Kinetics, Inc. The objective of this study was to examine the association between cognitive ability and gait initiation performance in older adults. Global and specific cognitive functions and spatiotemporal gait parameters during gait initiation were assessed in 60 older adults. Multivariate linear regression was conducted to determine the association between cognitive functions and gait initiation parameters. Results showed that global cognitive function was not associated with any of the spatiotemporal parameters. Poorer performance on measures of executive function and language ability were associated with shorter step length, narrower step width, and longer step time. In addition, poorer performance on test of visuospatial ability was associated with longer step time. In conclusion, specific but not global cognitive functions were associated with gait initiation performance. Clinical gait examination should incorporate gait initiation and cognitive assessments. Rehabilitation strategies aimed at improving cognition and gait initiation performance may be beneficial for preventing falls.